3D Microfluidic Surface‐Enhanced Raman Spectroscopy (SERS) Chips Fabricated by All‐Femtosecond‐Laser‐Processing for Real‐Time Sensing of Toxic Substances. (23rd April 2018) - Bai, Shi; Serien, Daniela; Hu, Anming; Sugioka, Koji
Abstract: A novel all‐femtosecond‐laser‐processing technique is proposed for the fabrication of 2D periodic metal nanostructures inside 3D glass microfluidic channels, which have applications to real‐time surface‐enhanced Raman spectroscopy (SERS). In the present study, 3D glass microfluidic channels are fabricated by femtosecond‐laser‐assisted wet etching. This is followed by the space‐selective formation of Cu‐Ag layered thin films inside the microfluidic structure via femtosecond laser direct writing ablation and electroless metal plating. The Cu‐Ag films are subsequently nanostructured by irradiation with linearly polarized beams to form periodic surface structures. This work demonstrates that a double exposure to laser beams having orthogonal polarization directions can generate arrays of layered Cu‐Ag nanodots with dimensions as small as 25% of the laser wavelength. The resulting SERS microchip is able to detect Rhodamine 6G, exhibiting an enhancement factor of 7.3 × 10 8 in conjunction with a relative standard deviation of 8.88%. This 3D microfluidic chip is also found to be capable of the real‐time SERS detection of Cd 2+ ions at concentrations as low as 10 ppb in the presence of crystal violet. This technique shows significant promise for the fabrication of high performance microfluidic SERS platforms for the real‐time sensing of toxic substances with ultrahigh sensitivity. Abstract : A novel 3D glass surface‐enhanced Raman spectroscopy (SERS) microfluidic chip is fabricated by an all‐femtosecond‐laser‐processing technique. 2D periodic Cu‐Ag nanodots are generated for SERS probes through femtosecond‐laser‐induced orthorhombic surface structures. This technique shows significant promise for the fabrication of a high‐performance microfluidic SERS platform for the real‐time online sensing of toxic substances with ultrahigh sensitivity.